A Chiral Naphthyridine Diimine Ligand Enables Nickel‐Catalyzed Asymmetric Alkylidenecyclopropanations. (10th July 2020) - Braconi, Elena; Cramer, Nicolai
Abstract: A novel class of chiral naphthyridine diimine ligands (NDI*) readily accessible from C2 ‐symmetric 2, 6‐di‐(1‐arylethyl)anilines is described. The utility of these ligands, particularly one with fluorinated aryl side arms, is demonstrated by a reductive Ni‐catalyzed enantioselective alkylidene transfer reaction from 1, 1‐dichloroalkenes to olefins. This transformation provides direct access to a broad range of synthetically valuable alkylidenecyclopropanes in high yields and enantioselectivities. Abstract : A class of chiral naphthyridine diimine ligands (NDI* ) is described. The application potential of these ligands for asymmetric catalysis is illustrated by a reductive enantioselective bi‐nuclear nickel‐catalyzed alkylidene transfer of 1, 1‐dichloroalkenes to olefins, yielding synthetically valuable alkylidenecyclopropanes in high yields and enantioselectivities.